2016
DOI: 10.1097/mpa.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Lithotripsy for Chinese Patients With Pancreatic Stones

Abstract: Thus, ESWL is a safe and effective method to treat Chinese patients with pancreatic stones. This procedure can significantly improve the success rate of endotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 38 publications
1
59
0
Order By: Relevance
“…The risk of complications relating to P‐ESWL was not increased in geriatric patients, and the efficacy of P‐ESWL was demonstrated by the significant pain relief and effective stone clearance. The outcome was similar to the results of previous P‐ESWL studies in young patients …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The risk of complications relating to P‐ESWL was not increased in geriatric patients, and the efficacy of P‐ESWL was demonstrated by the significant pain relief and effective stone clearance. The outcome was similar to the results of previous P‐ESWL studies in young patients …”
Section: Discussionsupporting
confidence: 89%
“…P‐ESWL has been successfully applied in the treatment of pancreatic stones since 1987 and is now recommended as the first‐line therapy for young patients with uncomplicated painful CP and radiopaque stones ≥ 5 mm obstructing the MPD . The safety and efficacy of P‐ESWL have been demonstrated in numerous studies, but data for geriatric patients have not been previously reported . Our study is the first to report the safety and efficacy of P‐ESWL in geriatrics.…”
Section: Discussionmentioning
confidence: 83%
“…1 In biliary stones ESWL, first reported in 1989, is successful in clearing 84-89% of stones, with cholangitis as the main adverse effect. 8,9 Recently, a prospective study including 214 chronic pancreatitis patients showed similar MPD clearance rates, with a 4% complication rate reported. 10 This study also showed that more than 50% of patients needed at least two ESWL sessions and up to 11% needed more than 4 sessions prior to removal of stones with ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…P‐ESWL was first used to remove pancreatic stones in 1987 . As a safe and effective non‐invasive therapeutic modality for the treatment of pancreatic stones, P‐ESWL is now the accepted standard of care for the management of large pancreatic stones all over the world . Since P‐ESWL acts on pancreatic stones via cavitation, and shear, resulted in stone fragmentation; these forces may lead to the injury of adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…5 As a safe and effective non-invasive therapeutic modality for the treatment of pancreatic stones, P-ESWL is now the accepted standard of care for the management of large pancreatic stones all over the world. 1,6,7 Since P-ESWL acts on pancreatic stones via cavitation, and shear, resulted in stone fragmentation; these forces may lead to the injury of adjacent tissues. To our knowledge, bleeding after P-ESWL includes hilar hematoma, hemorrhagic pseudoaneurysm in the pancreatic pseudocyst, mesenteric hemorrhage and hepatic subcapsular hematoma.…”
Section: Journal Of Digestive Diseases 2018; 19; 314-317mentioning
confidence: 99%